2000
DOI: 10.1108/02656710010298562
|View full text |Cite
|
Sign up to set email alerts
|

Service quality and product quality in housing refurbishment

Abstract: The significance of the quality of work in the construction industry has been highlighted in recent years. Nevertheless, it is unusual to find that housing refurbishment projects have been undertaken with a clear emphasis on the service provided for tenants. To assess the scope for tenant satisfaction in the refurbishment industry, an empirical study has been undertaken in an attempt to identify principles which have implications for housing refurbishment. The relationship between service quality, product qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
1
7
0
5
Order By: Relevance
“…The better the service quality provided by the bank the more loyal the customer to the bank will be. This is in line with studies of Cronin dan Taylor (1992), Zeithaml and Bitner (1996), Bloemer, et.al (1998), Lassar et al(2000), Natalisa (2000), Holm (2000), Bei dan Chian (2001), Astuti (2001), Kadir (2001), Fullerton dan Taylor (2002), Caruana (2002), Said (2004) that concluded that service quality has significant direct and indirect effects on customer loyalty mediated by customer satisfaction.…”
Section: Literature Reviewsupporting
confidence: 87%
“…The better the service quality provided by the bank the more loyal the customer to the bank will be. This is in line with studies of Cronin dan Taylor (1992), Zeithaml and Bitner (1996), Bloemer, et.al (1998), Lassar et al(2000), Natalisa (2000), Holm (2000), Bei dan Chian (2001), Astuti (2001), Kadir (2001), Fullerton dan Taylor (2002), Caruana (2002), Said (2004) that concluded that service quality has significant direct and indirect effects on customer loyalty mediated by customer satisfaction.…”
Section: Literature Reviewsupporting
confidence: 87%
“…Hasil studi ini mendukung studi yang dilakukan Holm (2000), Bei dan Chian (2001), dan Hidayat (2006) bahwa kualitas produk berpengaruh langsung terhadap kepuasan konsumen.…”
Section: Hasil Dan Temuanunclassified
“…Hasil studi ini mendukung studi yang dilakukan Holm (2000), Bei dan Chian (2001), dan Hidayat (2006) bahwa …”
Section: Metodologiunclassified